HUKUM DAN MASYARAKAT ADAT: TELAAH SOSIOLOGI HUKUM - Adinda Akhsanal Viqria; Nabila Zatadini; Muhammad Galib Iqbal (Legalita, 2023)
Abstract: The prevailing norms in indigenous peoples are important in social control in certain community groups. The law and indigenous peoples are closely related because they contain means that become references in solving problems in the groups of society. Things related to law in indigenous peoples arise from customs passed down from generation to generation over time. This article discusses the close relationship of law with indigenous peoples. In the discussion in this article, two points are drawn, which are studied through the point of view of the sociology of law, namely (1) the presence of law in indigenous peoples and (2) the rights and position of law in indigenous peoples. The form of discussion in this article is based on an analysis of previous research related to law and indigenous peoples. In its development, customary law can develop with national legal rules and values if it is extracted from the legal matters present in the community. Keywords: Customary law, indigenous peoples, sociology of law